2019
DOI: 10.1111/imj.14085
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism associated with therapy for multi‐drug‐resistant tuberculosis in Australia

Abstract: Prothionamide/PAS treatment-associated hypothyroidism is common in MDR-TB patients in Australia, emphasising the importance of regular thyroid function monitoring during this treatment. Thyroid hormone replacement if initiated, may not need to be continued after MDR-TB treatment is completed. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
(42 reference statements)
0
7
0
1
Order By: Relevance
“…Studies included in this review were reported from 19 countries which cover three continents (Africa, Asia and Europe) [Table 1]. Seventeen studies were reported from Asian [32,3440,4244,46,48,53,54,60,61], eight from African [41,45,47,49,50,55,57,58] and five from European [33,48,52,56,59] countries. We categorized Russia, Turkey and Ukraine under European countries category.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies included in this review were reported from 19 countries which cover three continents (Africa, Asia and Europe) [Table 1]. Seventeen studies were reported from Asian [32,3440,4244,46,48,53,54,60,61], eight from African [41,45,47,49,50,55,57,58] and five from European [33,48,52,56,59] countries. We categorized Russia, Turkey and Ukraine under European countries category.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies [32,36,37,39,51,54] used immunoassay based techniques as the method to measure TSH concentration, while 14 studies [38,41,42,44,46,47,49,5561] retrieved the value of TSH concentration from record (treatment card or laboratory report). However, ten studies [3335,40,43,45,48,50,52,53] did not report how TSH concentration was measured, and from where data on TSH concentration was collected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding was similar with the study reported by Ben-nan et al in 2020 (71.4%) from China in which prothionamide and para-aminosalicylic acid were significantly associated with hypothyroidism. 25 Moreover, the study reported by Cheung et al (2019) from Australia 34 indicated the significant association between prothionamide and hypothyroidism in MDR-TB patients on treatment.…”
Section: Discussionmentioning
confidence: 98%